THE OPTIMIZATION ON THE DISSEMINATION OF POROUS CARBONATE ROCKS AT ÃâÃâBILLYÃâÃâ FIELD NORTHEAST JAVA BASIN - RIZKI NAJI (NIM: 12313001), FAUZAN
The economic growth and increased of human needs impact to the need of energy. Oil and natural gas are the common energy used by human. The large public demand for fossil energy should be followed by the mount in exploration activities using geological and geophysical approaches to explore for zones that have the prospect of producing hydrocarbons. The Northeast Java basin is one of the areas with hydrocarbon prospects in Indonesia. The target of this research is in Kujung Formation. In this formation, the constituents are dominated by limestone deposited at the time of the Late Oligocene to the Early Miocene. Exploration activities continue to increase in this formation. In mapping of carbonate rock in this research, inversion seismic method is used to know the subsurface condition. The result of post stack seismic inversion is limited to produce acoustic impedance. Thus, it is necessary to optimize the result of post stack inversion. The inversion method used is a model based inversion and linear programming Sparse Spike Inversion. The result of seismic inversion model based tends to produce high frequency. While the result of LPPS inversion tends to produce low frequency. Therefore the result of both inversions will be processed with frequency domain merge. The inversion result of Acoustic Impedance will be used to make volume of porosity to determine porous carbonate zone.